Inclusivity-based intervention to enhance religious tolerance among junior high school students - Ali Mashuri; Sukma Nurmala; Ika Herani; Yuliezar Perwira Dara; Esti Zaduqisti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
This community service program is inspired by indications or trends of religious intolerance among students in Indonesia. We designed this community service as a preventive intervention to enhance the understanding and levels of religious tolerance among junior high school students. The intervention emphasizes the importance of nationalism towards the Unitary State of the Republic of Indonesia (Indonesian: Negara Kesatuan Republik Indonesia/NKRI) and religious moderation as enhancing factors of religious tolerance. Fifty-eight students of SMPN 10 Kota Malang participated in the pre-test and post-test. Data analysis built upon paired sample t-tests with bootstrapping. The results indicated that, first, general knowledge scores regarding religious tolerance (e.g., the meaning or definition of religious tolerance, positive impacts of religious tolerance) and specific knowledge about forms of religious tolerance were significantly higher at the post-test stage compared to the pre-test. Secondly, the intervention proved effective in enhancing religious tolerance, particularly in terms of interreligious respect and politics, as their scores at the post-test stage were significantly higher compared to the pre-test. The third finding showed that participants positively evaluated the community service activities in terms of their objectives, implementation, and outcomes. Participants also perceived the community service activities as beneficial in fulfilling their need for a better understanding of religious tolerance. Overall, the empirical findings in this community service program imply that inclusivity in society plays a crucial role in enhancing religious tolerance among junior high school students.